Effects of artificial aging conditions on yttria-stabilized zirconia implant abutments - Basílio, Mariana de Almeida; Cardoso, Kátia Vieira [UNESP]; Antonio, Selma Gutierrez [UNESP]; Rizkalla, Amin Sami; Santos Junior, Gildo Coelho; Arioli Filho, João Neudenir [UNESP] (Elsevier, 2016)
Statement of problem Most ceramic abutments are fabricated from yttria-stabilized tetragonal zirconia (Y-TZP). However, Y-TZP undergoes hydrothermal degradation, a process that is not well understood. Purpose The purpose of this in vitro study was to assess the effects of artificial aging conditions on the fracture load, phase stability, and surface microstructure of a Y-TZP abutment. Material and methods Thirty-two prefabricated Y-TZP abutments were screwed and tightened down to external hexagon implants and divided into 4 groups (n = 8): C, control; MC, mechanical cycling (1×106 cycles; 10 Hz); AUT, autoclaving (134°C; 5 hours; 0.2 MPa); and TC, thermal cycling (104 cycles; 5°/55°C). A single-load-to-fracture test was performed at a crosshead speed of 0.5 mm/min to assess the assembly's resistance to fracture (ISO Norm 14801). X-ray diffraction (XRD) analysis was applied to observe and quantify the tetragonal-monoclinic (t-m) phase transformation. Representative abutments were examined with high-resolution scanning electron microscopy (SEM) to observe the surface characteristics of the abutments. Load-to-fracture test results (N) were compared by ANOVA and Tukey test (α=.05). Results XRD measurements revealed the monoclinic phase in some abutments after each aging condition. All the aging conditions reduced the fracture load significantly (P<.001). Mechanical cycling reduced the fracture load more than autoclaving (P=.034). No differences were found in the process of surface degradation among the groups; however, the SEM detected grinding-induced surface flaws and microcracks. Conclusions The resistance to fracture and the phase stability of Y-TZP implant abutments were susceptible to hydrothermal and mechanical conditions. The surface microstructure of Y-TZP abutments did not change after aging conditions.